Detailed study of ELAIS N1 field with the uGMRT – II. Source properties and spectral variation of foreground power spectrum from 300–500 MHz observations - Chakraborty A.; Roy N.; Datta A.; Choudhuri S.; Datta K.K.; Dutta P.; Bharadwaj S.; Intema H.; Choudhury M.; Pal S.; Choudhury T.R. (My University, 2025)
Understanding the low-frequency radio sky in depth is necessary to subtract foregrounds in order to detect the redshifted 21 cm signal of neutral hydrogen from the cosmic dawn, the epoch of reionization and the post-reionization era. In this second paper of the series, we present the upgraded Giant Metrewave Radio Telescope (uGMRT) observation of the ELAIS N1 field made at 300–500 MHz. The image covers an area of ∼1.8 deg2 and has a central background rms noise of ∼ 15 μJy beam−1. We present a radio source catalogue containing 2528 sources (with flux densities > 100 μJy) and normalized source counts derived from that. A detailed comparison of detected sources with previous radio observations is shown. We discuss flux-scale accuracy, positional offsets, spectral index distribution and correction factors in source counts. The normalized source counts are in agreement with previous observations of the same field, as well as model source counts from the Square Kilometre Array Design Study simulation. It shows a flattening below ∼1 mJy that corresponds to a rise in populations of star-forming galaxies and radio-quiet active galactic nuclei. For the first time, we estimate the spectral characteristics of the angular power spectrum or multi-frequency angular power spectrum of diffuse Galactic synchrotron emission over a wide frequency bandwidth of 300–500 MHz from radio interferometric observations. This work demonstrates the improved capabilities of the uGMRT. © 2019 The Author(s) Published by Oxford University Press on behalf of the Royal Astronomical Society